GAMBARAN PENGETAHUAN, STIGMA, DAN DISKRIMINASI MASYARAKAT KEPADA PENDERITA FILARIASIS LIMFATIK DI KOTA PEKALONGAN TAHUN 2018 - Agung Prabowo Kusumo; Mateus Sakundarno Adi; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Lymphatic filariasis is a disease that can cause socio-psychological problems by stigma and discrimination due to chronic manifestations suffered. Pekalongan City is still an endemic area of lymphatic filariasis, even after mass treatment for the past 5 years This can overcome the problem of stigma and renewal in patients with lymphatic filariasis who have become clinical manifests. The impact of things that are not easily recorded in epidemiological data and become a hidden burden. This study discusses understanding knowledge, stigma, and discussion in society. This type of research is a quantitative descriptive. Data collection was done through questionnaires and interviews were conducted with 109 people selected by accidental technique. The results show that society in Jenggot Village has 72 people (66,1%)knowledge, Stigmatized to sufferers do with of 53 people (48.6% and discrimination occurred with 51 people (46.8). Conclusion of this research there’s stigma and discrimination toward lymphatic filariasis patients.